Diabetes mellitus and dental diseases in a primary healthcare center of Callao Region: Diabetes mellitus y enfermedades odontológicas en un establecimiento del primer nivel de la Región Callao - Morales, Juan (2020)
Objectives: To determine the frequency of dental diseases in patients with type 2 diabetes mellitus (DM2). Materials and methods: Cross-sectional descriptive study based on a secondary source. DM2 patients attended in the dental service of a primary healthcare center of “Mi Peru” district in the Callao Region participated. Results: A total of 36 patients with DM2 were analyzed, with a mean age of 56.94 years (SD = 11.56; Range: 28 to 76). Of the sample, 88.9% (n = 32) were female, 50% (n = 18) were 60 years of age or older and 47.2% (n = 17) had secondary education. A 94.4% of patients with DM2 presented at least one dental disease. The main dental diseases were caries, periodontitis and acute gingivitis, which affected 69.4% (n = 25), 36.1% (n = 13) and 25% (n = 9), respectively. A 72.2% (n = 26) of patients had loss of a dental piece and 50% (n = 18) had at least one piece to extract. Conclusions: Dental conditions are widespread in patients with type 2 diabetes, caries being more frequent, followed by periodontitis and acute gingivitis; in addition to a high loss rate of dental pieces. Diabetes requires multidisciplinary and timely intervention. Keywords: Diabetes Mellitus, Type 2; Tooth Diseases; Stomatognathic Diseases; Peru (Source: MeSH, NLM).